Inhibiting Reductive Elimination as an Intramolecular Disulfide Dramatically Enhances the Thermal Stability of SAMs on Gold Derived from Bidentate Adsorbents - Rittikulsittichai, Supachai (Langmuir : the ACS journal of surfaces and colloids, 2018)
The bidentate aromatic adsorbate, 5-(octadecyloxy)-1,3-benzenedimethanethiol (R1ArmDT), with a specific design of extended S-S distance and a geometric constraint to resist cyclic disulfide formation was synthesized. The film formation and thermal stability of self-assembled monolayers (SAMs) derived from R1ArmDT were investigated and compared to those of SAMs derived from an analogous bidentate dithiol 2-(4-(octadecyloxy)-phenyl)propane-1,3-dithiol (R1ArDT), in which the two sulfur atoms can readily form a cyclic disulfide upon reductive elimination from the surface. Although the SAMs derived from R1ArmDT were less densely packed than those derived from R1ArDT, as judged by the data obtained by X-ray photoelectron spectroscopy and polarization modulation infrared reflection absorption spectroscopy, the SAMs derived from R1ArmDT were markedly more thermally stable than those derived from R1ArDT. The greater thermal stability of the R1ArmDT SAMs can be rationalized on the basis of the structure of the bidentate R1ArmDT headgroup, in which the two pendant sulfur atoms cannot access each other intramolecularly to form a cyclic disulfide upon reductive elimination from the surface